Thermal and hydraulic performances of a tube filled with various thermal conductivities of porous media. (February 2015) - Peng, C.; Ming, T.; Tao, Y.
Abstract: The present study aims to numerically investigate the influence of thermal conductivity of a porous medium ( ks ) on the Nusselt (Nu) and performance evaluation criteria (PEC) numbers of an enhanced tube for heat exchanger (ETfHE). This is accomplished with a porous medium partially inserted within the core flow of the tube under fully developed laminar flow for heat exchange. In this research we demonstrated four cases: two with air as the working fluid, one with water, and one with an assumed fluid whose density is a quarter of that of water while the other physical parameters remain the same. The packing ratio of the porous medium is 90%, the scope of Re is 25–2000, and the thermal conductivity of the porous medium ranges from 0.1 to 200 W/(m K). The simulation results show that, under the given working conditions, the Nu and PEC numbers of the ETfHE will neither increase monotonically with the thermal conductivity of the porous medium nor increase monotonically with the Reynolds ( Re ) number. These results are different from the conventional thinking that increasing the thermal conductivity of a porous medium will increase the overall performance of the ETfHE.